Inhaler sustainability in asthma and COPD care: a systematic review - Agnieszka Ignatowicz; Alice M Turner; Adeola Ayodotun Onasanya; Yaser Haider; Grace Peaston (BMJ Open)
Objective To evaluate inhaler sustainability in asthma and Chronic Obstructive Pulmomary Disease (COPD) by analysing how inhaler design typology, prescribing and usage patterns, disposal and recycling practices influence human health and environmental outcomes, using a People-Process-Product (PPP) framework to identify actionable opportunities for improvement.Design A systematic review was conducted in May 2024, with reporting structured around the PPP framework using narrative synthesis.Data sources MEDLINE, Scopus, Cochrane Library and relevant grey literature were searched for publications over the period from April 2014 to April 2024.Eligibility criteria Studies were included if published between 2014 and 2024, involved patients with asthma or COPD and healthcare professionals and specifically examined aspects of inhaler sustainability, including patient behaviours, healthcare provider prescribing practices and environmental impacts.Data extraction and synthesis Two independent reviewers screened and extracted data from 63 studies. Due to diverse methodologies, quality assessment focused on research design robustness, completeness of outcome reporting and potential biases. Findings were synthesised narratively to address each research question using the PPP framework.Results 33% of included studies focused on two or more domains of the PPP framework as both primary and/or secondary outcomes. Studies mapped to the ‘People’ domain (n=34) showed limited awareness among patients and clinicians regarding the environmental impact of inhaler prescription patterns, use patterns and disposal methods, with over 75% of patients discarding inhalers in household waste. In the ‘Process’ domain (n=11), switching from pressurised metered-dose inhalers (pMDIs) to dry powder inhalers (DPIs) or soft mist inhalers (SMIs) was associated with improved inhaler adherence and asthma control, though uptake of new inhalers was influenced by patients’ prior experience, competence, proficiency and perceived usability. The ‘Product’ domain (n=41) showed that DPIs and SMIs consistently had lower carbon footprints than pMDIs, with short-acting beta-agonists (SABAs) pMDIs having the highest emissions due to prescription, use patterns and disposal.Conclusions Improving patient education on sustainable inhaler use and disposal and providing healthcare professionals with focused training on low-carbon prescribing are critical steps towards achieving significant clinical benefits and supporting environmental sustainability in asthma and COPD management.PROSPERO registration number CRD42024541927.